Here Is the Boke Of Mayd Emlyn That Had .V. Husbandes and All Kockoldes She Wold Make Theyr Berdes Whether They Wold Or No / and Gyue Them To Were a Praty Hoode Full Of Belles - Imprinted by John Skot (Imprinted by John Skot, 1525)
eebo-0113
Published [ca. 1525].
Keywords: English literature